Basic Financial Education for Migrant Youth: Applying Accounting in Daily Life - Samsinar, Samsinar; Tangke, Paulus; Burhanuddin, Burhanuddin; Rayyani, Wa Ode; Wijaya, Cinby Cantika (PT Inovasi Pratama Internasional, 2025)
This community engagement program aims to enhance the financial literacy of migrant youth by introducing basic financial education and the application of accounting in daily life. The activity was conducted with 32 participants from Angkatan Belia Islam, Pulau Penang, Malaysia, and facilitated by a team of lecturers from Universitas Negeri Makassar, Atma Jaya University Makassar, and Universitas Muhammadiyah Makassar. The method included pretest, material presentation, interactive discussion, posttest, and feedback sessions. Results of the pretest showed that the average participants’ understanding was below 60%, indicating limited knowledge of fundamental financial concepts such as distinguishing between needs and wants, recording expenses, and planning simple budgets. After the material presentation and discussion, posttest results demonstrated a significant increase in understanding across all indicators, with average scores exceeding 80%. The improvement reflects the effectiveness of the interactive and contextual teaching approach, particularly the use of relatable illustrations and ice-breaking games. The program not only improved participants’ financial literacy but also encouraged the application of accounting principles in their daily decision-making. These findings suggest that practical and participatory financial education initiatives are essential in empowering migrant youth to manage personal finances effectively and build financial independence.